Efficient purification of high‐purity compounds from the stem of Lonicera japonica Thunb using two‐dimensional preparative chromatography. Issue 15 (5th August 2013) - Jin, Hongli; Liu, Yanfang; Feng, Jiatao; Guo, Zhimou; Wang, Chaoran; Zhong, Zhengsheng; Peng, Xiaojun; Dang, Jun; Tao, Yanduo; Liang, Xinmiao
Abstract : Purification of high‐purity compounds from traditional Chinese medicines (TCMs) plays an important role in investigating their bioactivity. Nevertheless, it is often quite difficult to isolate compounds with high purity because of the complexity of TCMs in chemical composition. In this work, a two‐dimensional preparation method was successfully developed for the preparation of high‐purity compounds from the stem of Lonicera japonica Thunb, based on two novel polar copolymerized RP stationary phases, XAqua C3 and XAqua C18. An XAqua C3 prep column was used to separate the sample in the first‐dimensional preparation, and 14 g of sample was fractionated into eight fractions with a recovery of 82%. An XAqua C18 prep column was selected to prepare high‐purity compounds in the second‐dimensional preparation for its good orthogonality with the XAqua C3 stationary phase. As a result, major compounds in the sample were isolated with more than 99% purity. This method is a potent method to realize the efficient purification of compounds with high purity from the stem of L. japonica Thunb and it shows great potential in the separation of high‐purity compounds from complex samples.